A Thomas Hardy dictionary with maps and a chronology - Pinion, F. B. (Houndmills Macmillan Press, 1989)
This dictionary provides explanations of references and rare words or words used with rare meanings, sources of quotations and allusions, identifications of fictional places and people with critical and informative comments on all Hardy's novels and short stories, his drama, at least 500 of his poems, his major symbols and important influences on this thought and creativity which constitute the bulk of this work. It intends to provide insight and guidance on many questions, from those arising incidentally to those which are more pervasive; for example on meliorism, chance, Old Style reckoning, the eleventh commandment, the origins of Poorgrass's multiplying eye, and of the Shockerwick Houe scene, the location of Lewgate, and the significance of the title "Where Three Roads Joined". Notes are given for Hardy's prefaces and most important essays and links with his life are made throughout. The author has written "A Hardy Companion", "Thomas Hardy: Art and Thought", "A Commentary on the Poems of Thomas Hardy" (with Evelyn Hardy), "One Rare Fair Woman" as well as works on Jane Austen, the Brontes, George Eliot, D.H. Lawrence, Wordsworth, Tennyson and T.S. Eliot.
Keywords: Hardy, Thomas, 1840-1928 -- Dictionaries